Correlation of the flipped classroom learning and motivation on Mathematics learning outcomes - Anna Herlina; Khasanah Khasanah; Eka Yunita Yustantina; Pardan Prasetyo; Yunea Kusuma Winanti (Inovasi Kurikulum, 2026)
Improving students' learning motivation should be a consideration for teachers when implementing learning activities. The objectives of this study were to 1) determine the relationship between the flipped classroom learning method and Mathematics learning outcomes; 2) determine the relationship between motivation and Mathematics learning outcomes; 3) determine the relationship between the flipped classroom learning method and motivation together with Mathematics learning outcomes. This study involved sixth-grade students from several elementary schools in Bekasi City: SDN 02 Babelan (96 students), SDN 03 Babelan (48 students), and SDN 09 Babelan (84 students). The research approach used in this study was a preliminary survey, with regression and correlation analyses. The data collection techniques used in this study consisted of two: a Mathematics learning outcome test in the form of questions and a Likert-scale questionnaire. The results of the study showed that 1) there was a positive relationship between the application of the flipped classroom learning method and Mathematics learning outcomes; 2) there was a positive relationship between motivation and Mathematics learning outcomes; 3) there was a positive relationship between the flipped classroom learning method and motivation, together with Mathematics learning outcomes. The flipped classroom creates an environment where existing motivation is leveraged, and low motivation is addressed through engaging classroom activities and direct teacher support.   Abstrak Meningkatkan motivasi belajar siswa perlu menjadi pertimbangan bagi guru dalam menerapkan kegiatan pembelajaran. Tujuan penelitian ini adalah untuk 1) mengetahui hubungan antara metode pembelajaran kelas terbalik dan hasil belajar Matematika; 2) mengetahui hubungan antara motivasi dan hasil belajar Matematika; 3) mengetahui hubungan antara metode pembelajaran kelas terbalik dan motivasi secara bersama-sama dengan hasil belajar Matematika. Penelitian ini melibatkan siswa kelas VI di beberapa sekolah dasar di Kota Bekasi, yaitu SDN 02 Babelan dengan jumlah siswa 96 siswa, SDN 03 Babelan dengan jumlah siswa 48 siswa, dan SDN 09 Babelan dengan jumlah siswa 84 siswa. Pendekatan penelitian yang digunakan dalam penelitian ini adalah metode survei pendahuluan dengan teknik regresi dan korelasi. Teknik pengumpulan data yang digunakan dalam penelitian ini terdiri dari dua, yaitu tes hasil belajar matematika berupa soal-soal dan angket berupa skala Likert. Hasil penelitian menunjukkan bahwa 1) terdapat hubungan positif antara penerapan metode pembelajaran kelas terbalik dan hasil belajar matematika; 2) terdapat hubungan positif antara motivasi dan hasil belajar matematika; 3) terdapat hubungan positif antara metode pembelajaran kelas terbalik dan motivasi secara bersama-sama terhadap hasil belajar matematika. Kelas terbalik menciptakan lingkungan di mana motivasi yang sudah ada dimanfaatkan dan motivasi rendah diatasi melalui aktivitas kelas yang menarik serta dukungan langsung dari guru. Kata Kunci: luaran pembelajaran; Matematika; model kelas terbalik; motivasi belajar